Diagnostic accuracy of the Composite International Diagnostic Interview (CIDI 3.0) in an urban Indigenous Australian sample. (February 2023) - Basit, Tabinda; Anderson, Mathew; Lindstrom, Akiaja; Santomauro, Damian F; Whiteford, Harvey A; Ferrari, Alize J
Objective: The Composite International Diagnostic Interview 3.0 is a standardised diagnostic interview commonly used in population-based mental health surveys, but has not been used in community-residing Indigenous Australians. This paper seeks to determine whether the Composite International Diagnostic Interview 3.0 can produce valid diagnostic information when compared with a diagnostic interview in an urban Indigenous Australian sample. Method: This research was conducted over 10 weeks with adult Indigenous clients of two participating Aboriginal Medical Services in South-East Queensland. Using a cross-sectional, repeated-measures design, participants were administered the Composite International Diagnostic Interview 3.0 by an Indigenous interviewer and within 2 weeks attended a second appointment with an Indigenous clinical psychologist, who produced a diagnostic summary. The Composite International Diagnostic Interview 3.0 diagnoses were compared with the diagnostic summaries and clinical concordance between the two measures was calculated. Results: The diagnostic accuracy of the Composite International Diagnostic Interview 3.0 differed by module. The Post-traumatic Stress Disorder and Major Depression modules had good utility in diagnosing post-traumatic stress disorder and major depressive episodes, respectively; however, the Mania module that provides diagnoses of bipolar disorder was found to be unsuitable for this population. Although there were no identified contraindications for the use of the Generalised Anxiety and Alcohol Use Disorder modules, further research on the diagnostic accuracy of these modules is warranted. Conclusions: The Composite International Diagnostic Interview 3.0 can accurately diagnose some common mental disorders in an Indigenous Australian population, but was found to be unsuitable for others. Given these findings, care should be taken when using the Composite International Diagnostic Interview 3.0 in epidemiological prevalence studies with Indigenous Australian populations.